2016
DOI: 10.1186/s13612-016-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing in the Making: Peoples’ Experiences with Wearable Activity Trackers

Abstract: BackgroundWearable activity trackers have become a viable business opportunity. Nevertheless, research has raised concerns over their potentially detrimental effects on wellbeing. For example, a recent study found that while counting steps with a pedometer increased steps taken throughout the day, at the same time it decreased the enjoyment people derived from walking. This poses a serious threat to the incorporation of healthy routines into everyday life. Most studies aim at proving the effectiveness of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 40 publications
3
73
1
2
Order By: Relevance
“…This issue should be investigated before concluding that people give up on their walking routines based only on monitoring software. While using fitness tracking technology can lead to increases in self-monitoring, this may lose relevance over time when people get similar amounts of activity each day (100). Fitness trackers have the potential, however, to increase feelings of control over one’s own exercise behaviors (100).…”
Section: Factors Involved In Behavior Changementioning
confidence: 99%
See 1 more Smart Citation
“…This issue should be investigated before concluding that people give up on their walking routines based only on monitoring software. While using fitness tracking technology can lead to increases in self-monitoring, this may lose relevance over time when people get similar amounts of activity each day (100). Fitness trackers have the potential, however, to increase feelings of control over one’s own exercise behaviors (100).…”
Section: Factors Involved In Behavior Changementioning
confidence: 99%
“…While using fitness tracking technology can lead to increases in self-monitoring, this may lose relevance over time when people get similar amounts of activity each day (100). Fitness trackers have the potential, however, to increase feelings of control over one’s own exercise behaviors (100). This could actually increase the likelihood of sustained behavior change, as feeling in control of exercise behaviors can increase feelings of self-efficacy – a key predictor of physical activity adherence (24).…”
Section: Factors Involved In Behavior Changementioning
confidence: 99%
“…Regardless, wearable devices and mobile apps have vast potential to enhance motivation and fun [27], and sustained engagement in everyday life [28]. In a recent study, [29] compared real-life experiences of 133 users of three popular wearable activity trackers: Fitbit, Jawbone Up and Nike+ Fuelband. Utilizing need fulfilment as a theoretical lens, the study revealed that UX is driven by the needs of physical thriving or relatedness.…”
Section: Fitness Tracking Ux and Self-determination Theorymentioning
confidence: 99%
“…In [42] authors identified five use cases for data from long term self-monitoring: (1) supporting health behavior, (2) improved health understanding, (3) identification of trends and relations, (4) making informed decisions, and (5) storing data for future use. Other researchers addressing long-term use of tracking point into similar directions [33,27].…”
Section: Introductionmentioning
confidence: 99%